Unlocking innovation in the sport industry through additive manufacturing. Issue 3 (27th June 2019) - Meier, Marlon; Tan, Kim Hua; Lim, Ming K.; Chung, Leanne
Abstract : Purpose: Fast-changing customer demands and rising requirements in product performance constantly challenge sports equipment manufacturers to come up with new and improved products to stay competitive. Additive manufacturing (AM), also referred to as 3D printing, can enhance the development of new products by providing an efficient approach of rapid prototyping. The purpose of this paper is to analyse the current adoption of AM technologies in the innovation process of the sports industry, i.e. level of awareness; how it is implemented; and it impact on the innovation process. Design/methodology/approach: This work followed a qualitative research approach. After conducting a research of the current literature, this paper presents findings that include case studies from different companies, as well as a semi-structured interview with an outdoor sports equipment manufacturer. Companies from all over the world and of different sizes from under 100 employees to over 70, 000 employees were considered in this research. Findings: Literature research shows that AM brings many possibilities to enhance the innovation process, and case studies indicated several obstacles that hinder the technology from fully unfolding. AM is still at the early stage of entering the sports equipment industry and its potential benefits have not been fully exploited yet. The findings generated from the research of real-life practices show that AM provides several benefits when it comes to the innovation process, such as a faster development process, an optimised output, as well as the possibility to create new designs. However, companies are not yet able to enhance the innovation process in a way that leads to new products and new markets with AM. Limitations, including a small range of process able material and an inefficient mass production, still restrain the technology and lead to unused capability. Nevertheless, future prospects indicate the growing importance of AM in the innovation process and show that its advancement paves the way to new and innovative products. Research limitations/implications: Limitations exist in the qualitative approach of this study, which does not include the quantitative verification of the results. Originality/value: Very few studies have been conducted to investigate how firms can harvest AM to increase their innovation capabilities. How firms can use AM to shorten product development time is an emerging topic in business and operations but has not been studied widely. This paper aims to address this gap.